Language and Quality Assurance: A Case Study Highlighting the Effects of Power, Resistance, and Countertactics in Academic Program Reviews - Bowker, Lynne (TTR)

(untitled) (Association canadienne de traductologie, 2016)
Quality assurance has been recognized as being important in higher education; however, there are numerous reports that it is challenging to engage faculty members in quality assurance processes in a meaningful way. A frequently cited reason for faculty members’ resistance is that they find the process to be authoritarian and non-collegial. This paper presents a case study which shows that changing the tone of the language used to communicate with academics about the institutional quality assurance process—from a bureaucratic and authoritative tone to a more collegial one—can serve as a countertactic to help mitigate the resistance of faculty members to this process. Using corpus-based techniques, we investigate the language used in documents to communicate with faculty members about quality assurance. We then demonstrate that, following a linguistic revision to introduce a more collegial tone to these communications, faculty members appear to be more willing to engage in the quality assurance process in a meaningful way.